THE ROLE OF SEAWEED (Gracilaria verucosa) IN CO-CULTIVATION WITH TIGER SHRIMP (Penaeus monodon) AS AN ECOLOGICAL INTENSIFICATION - Lestari Lakhsmi Widowati; Tita Elfitasari; S Budi Prayitno; Sri Rejeki; Pujiono W Purnomo; Restiana W Ariyati; Roel Bosma (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2020)
The use of seaweed as ecological tools for improving environmental condition has been proved to sustain shrimp production. However, adding too much seaweeds caused oxygen depletion and nutritional competition. The objective of this study was to determine the optimum density of G. verucosa for supporting the growth of monodon shrimp. The research was conducted in Tambakbulusan village, Demak Regency with 20 fiber semi outdoor tanks. The tanks were used for the experiment without seaweed and with four densities of seaweed (50, 100, 150 and 200 g.m-2) using hanging rope and were co-cultivated with 80 individuals of post larva (2.0-2.9 g) monodon shrimp in 800 L brackish-water system. The concentration of TAN, NO3, and NO2 were monitored every week, while dissolved oxygen (DO), pH, temperature, and salinity werechecked daily for 30 days. The highest shrimp survival rate (79.75%) and growth rate (6.6%day-1) were obtained in the 100 g.m-2 of G. verucosa, significantly higher than in other treatments. Furthermore, seaweed density has a decreasing effect of NO3 content (g/L) in RL100 from 0.26 to 0.16. and the lowest concentration of NO2 and NO3 were determined. Conversely, the highest density of seaweed (200 g m-2) gave the lowest survival rate of shrimp (53.67%) due to high NO2 content. DO had various values depending on the density and drop to less than 3.5 ppm in the highest density. In all treatments,  pH, temperature and salinity werein a good range for shrimp culture. Thus, 100 g.m-2 of seaweed was optimal for ensuring the function as nutrient removal in shrimp co-culture.